Factors affecting fertilizer use efficiency in dry season paddy production in Makawanpur district, mid hill, Nepal - Thapa, M (Agronomy Journal of Nepal, 2013)
On-farm assessment of factors defining fertilizer use efficiency (FUE) for dry season paddy production was carried out through field survey and applying a two-step approach. The research was carried out in Makawanpur district, central mid hill, Nepal for the early rice (Chaite season) cropping season 2000. Data on land and land use aspects and yield record were collected through interview and field observation. Data entry, coding and normalization procedure were followed by stepwise regression analysis. In step one, the general regression model for causes of actual yield variations was derived; it included some land and management parameters that satisfactorily explained the variability of actual yields (adjusted R2 of 65 %). This model was used to calculate the adjusted yields by removing the impacts of non-fertilizer related variables from the actual yield data. In order to evaluate aspects of fertilizer use efficiency (step two), a stepwise regression produced a highly significant (adjusted R2 of 45%) result. The important factors defining FUE were the relationship between many parameters such as quantity of 1st N topdressing x soil pH, basal N x FYM, 1st N top dressing x good drainage condition, 2nd N top dressing x insect attack during tillering-flowering stage, 2nd N topdressing x soil pH, basal N x soil pH, FYM x soil pH, 1st N topdressing x FYM and 2nd N topdressing x zinc deficiency. Thus the study concluded that FUE is one of the critical issues that hindered sustainable paddy production. The timing and quantity of fertilizer especially N application, source of fertilizer, nutrient content combination, and their interactions with land and land use aspects were crucial elements for getting optimum response to fertilizer. DOI: http://dx.doi.org/10.3126/ajn.v1i0.7552 Agronomy Journal of Nepal (Agron JN) Vol. 1: 2010 pp.123-133